Physical Fitness Assistance and Economic Strengthening Using Light Emitting Diode Technology for Youth Forum RT 04/02 (Format) Marga Mulya Subdistrict Bekasi City - Truly Wangsalegawa; Juli Candra; Suharjudin; Desy Tya Maya Ningrum; Muhammad Ziddan Ali (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2024)
Community Service Activities were carried out in Marga Mulya Village, North Bekasi District, Bekasi City, in collaboration with the RT 04/02 Youth Forum, abbreviated as FORMAT. Community Service activities are carried out for 5 months by providing physical fitness assistance and economic strengthening to the younger generation in the form of training activities in developing physical abilities so that they can improve physical fitness abilities so that it is hoped that a strong generation can be born and able to avoid all the social diseases that can occur. destroying the future, as well as providing training in exploring the potential of the RT 04/02 Youth Forum (Format) to develop economic development capabilities, exploring the entrepreneurial potential that exists in the younger generation so as to create skilled young entrepreneurs and providing marketing strategies, analyzing market share and marketing management so as to produce quality products and be able to compete in society. Through community service activities, it is hoped that youth who are members of FORMAT will be able to become a better generation and be self-sufficient with the human resources they have and be able to respond well to change so that a physically strong generation is born. and strong economically.